Evaluation of 'Ask the Specialist': a cultural education podcast to inspire improved healthcare for Aboriginal peoples in Northern Australia. Issue 2 (4th May 2022) - Kerrigan, Vicki; McGrath, Stuart Yiwarr; Herdman, Rarrtjiwuy Melanie; Puruntatameri, Pirrawayingi; Lee, Bilawara; Cass, Alan; Ralph, Anna P.; Hefler, Marita
ABSTRACT: In Australia's Northern Territory (NT) most people who access health services are Aboriginal and most healthcare providers are non-Indigenous; many providers struggle to deliver culturally competent care. Cultural awareness training is offered however, dissatisfaction exists with the limited scope of training and the face-to-face or online delivery format. Therefore, we developed and evaluated Ask the Specialist: Larrakia, Tiwi and Yolŋu stories to inspire better healthcare, a cultural education podcast in which Aboriginal leaders of Larrakia, Tiwi and Yolŋu nations, known as the Specialists, answer doctors' questions about working with Aboriginal patients. The Specialists offer 'counterstories' which encourage the development of critical consciousness thereby challenging racist narratives in healthcare. After listening to the podcast, doctors reported attitudinal and behavioural changes which led to stereotypes being overturned and more culturally competent care delivery. While the podcast was purposefully local, issues raised had applicability beyond the NT and outside of healthcare. Our approach was shaped by cultural safety, critical race theory and Freirean pedagogy. This pilot is embedded in a Participatory Action Research study which explores strategies to improve culturally safe communication at the main NT hospital Royal Darwin Hospital.